â€œTANGLED IN MUSICAL MANGROVESâ€ - Kadek Indra Wijaya (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2012)
The realization of awork of artmust go through a process, namely thework of art. Processes in question are the stages of thework done since getting the idea to claimthat happen. In order for this processwentwell, it needs sincerity andmaturity of theconcept. The concept ofmusical Tangled inMangroves is howmusic can be presentedwhen themangroves began to tanglewith an array of abrasion is performed by humans.With the perspective of building the complex,which is processed into themangroves, then the author has a sense of hope that nature will stay in touch. Always accompany themusic flowing greenleaves and strong roots ofmangrove trees that gave birth to human social relationswith the natural harmony among fellowwill stay in touch.Keywords: concepts, processes,mangroves,music